Gut Microbiome Alters the Activity of Liver Cytochromes P450 in Mice With Sex-Dependent Differences - Jourová, Lenka; Vavreckova, Marketa; Zemanova, Nina; Anzenbacher, Pavel; Langova, Katerina; Hermanova, Petra; Hudcovic, Tomas; Anzenbacherova, Eva (Frontiers in pharmacology, 2020)
Sexual differences and the composition/function of the gut microbiome are not considered the most important players in the drug metabolism field; however, from the recent data it is obvious that they may significantly affect the response of the patient to therapy. Here, we evaluated the effect of microbial colonization and sex differences on mRNA expression and the enzymatic activity of hepatic cytochromes P450 (CYPs) in germ-free (GF) mice, lacking the intestinal flora, and control specific-pathogen-free (SPF) mice. We observed a significant increase in the expression of Cyp3a11 in female SPF mice compared to the male group. However, the sex differences were erased in GF mice, and the expression of Cyp3a11 was about the same in both sexes. We have also found higher Cyp2c38 gene expression in female mice compared to male mice in both the SPF and GF groups. Moreover, these changes were confirmed at the level of enzymatic activity, where the female mice exhibit higher levels of functional CYP2C than males in both groups. Interestingly, we observed the same trend as with CYP3A enzymes: a diminished difference between the sexes in GF mice. The presented data indicate that the mouse gut microbiome plays an important role in sustaining sexual dimorphism in terms of hepatic gene expression and metabolism.